2021
DOI: 10.4103/ajns.ajns_180_20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgery on the survival of patients with recurrent glioblastoma

Abstract: Objective: The purpose of this study was to investigate the possible benefit of repeat surgery on overall survival for patients with recurrent glioblastoma multiforme (GBM). Methods: We performed a retrospective analysis of data from patients who presented with recurrent GBM over a 5-year period ( n = 157), comparing baseline characteristics and survival for patients who had at least 1 new tumor resection followed by chemotherapy (reoperation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…15 This highlights the need for individualized decision-making based on patient characteristics and tumor features. The literature presently has only opinions and case series for re-surgery, [16][17][18] and a randomized controlled trial is essential.…”
Section: Discussionmentioning
confidence: 99%
“…15 This highlights the need for individualized decision-making based on patient characteristics and tumor features. The literature presently has only opinions and case series for re-surgery, [16][17][18] and a randomized controlled trial is essential.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of management strategies for rGBM were explored. Re-resection was proved to be a favorable independently prognostic factor for rGBM [24][25][26][27]. In Ringel's study [9], the median OS of patients who received re-operation without considering IDH1 status was 11.9 months.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled results from four studies [14], [28], [31], [32] showed a statistically significant ratio of mortality in female as compared to males (HR= 1.19 [1.06, 1.34]; p = 0.002; I 2 = 0%).…”
Section: Effect Of Gender In Prognosis Of Glioblastoma Multiforme Pat...mentioning
confidence: 99%